2015
DOI: 10.3389/fpsyg.2015.00831
|View full text |Cite
|
Sign up to set email alerts
|

Comparing personal insight gains due to consideration of a recent dream and consideration of a recent event using the Ullman and Schredl dream group methods

Abstract: There have been reports and claims in the psychotherapeutic literature that the consideration of recent dreams can result in personal realizations and insight. There is theoretical support for these claims from work on rapid eye movement (REM) sleep having a function of the consolidation of emotional memories and the creative formation of connections between new and older memories. To investigate these claims, 11 participants (10 females, one male) reported and considered a recent home dream in a dream discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 82 publications
(107 reference statements)
1
20
0
Order By: Relevance
“…For this reason, the dreamer should have privileged insight into meaningful dream associations, which is not equivalent to asserting that the dreamer is necessarily correct. Hill et al ( 1993 ) found interpreting one's own dream engendered more insight than interpreting that of another person, see also Edwards et al ( 2013 ) and Edwards et al ( 2015 ) for dream insight studies.…”
Section: Illustrative Dream - “Bagpuss”mentioning
confidence: 99%
“…For this reason, the dreamer should have privileged insight into meaningful dream associations, which is not equivalent to asserting that the dreamer is necessarily correct. Hill et al ( 1993 ) found interpreting one's own dream engendered more insight than interpreting that of another person, see also Edwards et al ( 2013 ) and Edwards et al ( 2015 ) for dream insight studies.…”
Section: Illustrative Dream - “Bagpuss”mentioning
confidence: 99%
“…Sleep processes – and we would argue, the concomitant subjective experience of dreaming – enabled the hyperassociativity of the information that was already stored to be used in a creative and useful way. Similarly, working with dreams has been shown to generate insight into the self ( Edwards et al, 2013 , 2015 ), and more insight is obtained when participants are asked to make associations between the dream images and waking life than when simply richly describing the dream images (or a combination of the two: Hill et al, 1998 ). Perhaps then the idea of dreams telling us “something we don’t already know” should be restated as “something we are not aware of knowing,” in which ‘knowing’ may constitute formerly disparate pieces of information that require reconfiguring to become useful.…”
Section: The Emotion Assimilation Theory Of Sleep and Dreamingmentioning
confidence: 99%
“…Intuitions may come to the surface of consciousness suddenly, as a “hunch,” the sudden perception of a pattern in seemingly unrelated events, or as creative discovery.” From this statement, we can see that N types may be more able to find correlations between the waking source domain and the dream domain. Previous evidence shows that consideration of the relationship between waking experiences and dreams can bring out insights and benefits ( Hill et al, 1998 ; Edwards et al, 2013 , 2015 ). So N types’ advantage to find correlations could give them more insights and benefits than S types.…”
Section: Discussionmentioning
confidence: 99%